PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Indi Rahmawati, Pipit; Dede Salim Nahdi; Yeni Dwi Kurino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This research is motivated by the low critical thinking ability of fifth grade students of SDN Talaga Wetan III, Talaga District, Majalengka Regency. One of the causes is the inaccuracy of the model used by the teacher. The purpose of this study is to determine the effect of the Realistic Mathematic Education model on students' critical thinking abilities. The type of research conducted is an experiment, with the design used being a quasi-experiment, with a nonequivalent control group design. Where there are two groups given different treatments. The population used is fifth grade of SDN Talaga Wetan III and fifth grade of SDN Banjaran, totaling 39 students with a nonprobability sampling technique of saturated sample type. The instrument used in this study is a descriptive test. The results of the study obtained data analysis scores using the average posttest results of the experimental class is 76.65 the average control result is 54.89, then a difference of 21.76 is seen. Based on the results of the hypothesis test analysis using the Independent Sample T Test with a significance level of 0.05, which is 0.001 <0.05 so that Ha is accepted. This means there was a difference in post-test results in the control class. These results suggest that the Realistic Mathematics Education model has an impact on students' critical thinking skills. This indicates that there is a difference in the Realistic Mathematics Education model's effects.